Maternal transmission of interstitial 8p23.1 deletion detected during prenatal diagnosis1. Issue 1 (14th December 2012) - Guimiot, F.; Dupont, C.; Fuentes‐Duarte, A.; Aboura, A.; Bazin, A.; Khung‐Savatovsky, S.; Tillous‐Borde, I.; Delezoide, A.‐L.; Azancot, A.
Abstract We report on the first prenatally diagnosed interstitial 8p23.1 maternally inherited deletion. At 20 weeks of gestation (WG) the fetus was diagnosed with a complete atrioventricular canal. In infancy, the mother underwent a two‐step cardiac surgery for an interrupted aortic arch type A associated to an inlet ventricular septal defect (VSD). A straddling of the tricuspid valve type B was confirmed during surgery. The outcome showed no cardiac failure or conduction anomalies. However, she presented with moderate intellectual disability. Classical and molecular cytogenetic studies on amniotic and maternal lymphocytes cells showed a nearly identical interstitial deletion of the 8p23.1 region encompassing the GATA4 gene locus (Mother: nt 6, 913, 337–12, 580, 828, fetus: nt 7, 074, 449–12, 580, 828) with no modification of the telomeric region. The relevance of our report is not only the maternal syndromic interstitial 8p23.1 deletion, but also maternal transmission which has never been reported before. The maternal and fetal phenotypes were not identical, however, even though they had the same cellular and molecular background: an alteration of the epithelial mesenchymal transition of the atrioventricular valvulo‐septal complex where GATA4 plays a positive role in the regulation. We reviewed all cases of interstitial 8p23.1 deletions diagnosed either prenatally or postnatally. © 2012 Wiley Periodicals, Inc.